Placental recent/on-going foetal vascular malperfusion with endothelial fragmentation is diagnostically equivalent to established distal villous lesions of foetal vascular malperfusion - Jerzy Stanek (Polish Journal of Pathology, 2023)
CD34 immunostaining increases the sensitivity of placental diagnosis of foetal vascular malperfusion (FVM). This comparative retrospective study was performed to find out whether recent distal FVM lesions diagnosed with CD34 are diagnostically equivalent to remote FVM lesions diagnosed with haematoxylin-eosin (H&E). Clinical and placental phenotypes of 562 placentas from ≥ 20-week, high-risk pregnancies were analysed: Group 1–158 placentas with remote distal villous FVM (by H&E only), Group 2–142 placentas showing clustered endothelial fragmentation by CD34 immunostaining, 98 of them also with H&E distal FVM lesions (on-going, temporal heterogeneity), and Group 3–262 placentas without distal villous FVM. In Group 1, gestational age was the shortest, postnatal mortality most frequent, placental weight the smallest, and intra villous haemorrhage, erythroblasts in foetal blood, hypertrophic decidual arteriopathy, and foetal vascular thrombi most common. In Group 2, placental infarction, post-uterine pattern of chronic placental injury, and excessive extra villous trophoblasts of chorionic disc were most common (p < 0.05). In this cohort of foetuses/neonates dominated by congenital malformations, distal villous FVM was the most common pattern of placental injury, and those diagnosed by CD34 and by H&E are diagnostically/prognostically equivalent. CD34 immunostaining is therefore a powerful tool in the diagnosis of distal villous FVM.